Analysis of Motivation And Learning Interest In The English Speaking Ability of Madrasah Tsanawiyah Students - Purwo Haryono (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aimed to determine the motivation and interest in learning students' English speaking abilities. This research uses quantitative research. This study also uses the correlational method to examine the contribution between research variables. The variables of this study consist of three, namely: motivation (X1) and interest in learning (X2) are the independent variables, and the ability to speak English (Y) is the dependent variable. This research is located in every MTS student with a research sample of class X students totalling 30, 19 women and 11 men. The instrument used in collecting research data is a questionnaire. Data analysis is divided into three stages: data description, analysis requirements testing, and hypothesis testing. The results of the study can be drawn from the following conclusions. Based on the frequency distribution and percentage of class motivation (X1) (N=30), most students have external motivation, namely 20.4%. Students with moderate motivation, 38.3%, and some others are included in the high category, namely 30.9 %. Based on the frequency distribution and the percentage of interest in learning (X1). Based on class (N = 30), most students had moderate learning interests, namely 53.4%. Some other students were in the upper and lower classes, namely 25.4 and 25.2%, followed by a shallow type of 3.5%. In addition, students' interest in learning is included in the very high category, namely 2.4%. Based on frequency distribution and percentage of spoken English (Y) Based on scores (N=30), most students have moderate English proficiency, namely 40.57%, and some other students fall into the high and low categories, namely 20.3% and 23.4% attended by regular class only. At least 6.59%. Not only that but in the very high sort, no students could speak English.